Evaluating elbow joint kinematics with the Stewart Platform Mechanism - Alrashidi, M.; Yildiz, I.; Alrashdan, K.; Esat, I. (WIT PRESS/COMPUTATIONAL MECHANICS PUBLICATIONS, 2009)
Joint measurement is necessary for studying joint laxity. Joint laxity in elbows is a problem which normally comes with age. However, it can increase to critical levels with rupture or damage to the ligaments of the elbow and affects the stability and capabilities of the joint, interfering even with daily activities. A new Stewart platform based elbow joint measurement was developed. The study focused on flexion, extension, valgus and varus motions and all experimental data were taken from a real experimental setup. The centre of rotation and motion of the angles of the forearm were found by the kinematics of the Stewart Platform Mechanism with a simmechanics based program algorithm. The joint motions of two male subjects were measured and the results of these measurements were compared with graphs. Comparisons demonstrate that the Stewart platform based measurement device sufficiently measures all motions of the elbow with six axes.
Keywords: joint laxity; Stewart platform; elbow kinematics; PASSIVE MOTION; Engineering